Expressive Speech Acts in the Kpu.Ri Instagram Comments - Ulfa Nafila; Rika Ningsih (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research delves into the multitude of expressive speech acts evident in the Instagram comment section of the KPU Statement concerning the 2024 Presidential and Vice Presidential Candidate Debate during the 2024 Election, particularly on the official KPU_RI Instagram account. It aims to address the prevalence and nature of these speech acts within the @KPU_RI Instagram comments. Employing a qualitative approach with content analysis methods, this study explores and elaborates on expressive speech acts in response to the KPU_RI Instagram post titled